The effects of pressure and temperature on the energy levels of a parabolic two-electron quantum dot in a magnetic field - Faten Bzour; Mohammad K. Elsaid; Khaled F. Ilaiwi (Journal of King Saud University: Science, 2018)
In the present work, we have calculated the energy levels of GaAs parabolic quantum dot under the combined effects of external pressure, temperature and magnetic field. The eigenenergies have been obtained by solving the two electron quantum dot Hamiltonian using the exact diagonalization method. The obtained results show that the energy levels of the quantum dot depend strongly on the pressure and temperature. We have found that the energy levels enhance as the pressure increases for fixed temperature and magnetic field while the quantum dot energy levels decrease as the temperature increases for fixed pressure and magnetic field. The comparisons show that our results are in very good agreement with the reported works.